Biocontrol Potential of a Native Trichoderma Collection Against Fusarium oxysporum f. sp. cubense Subtropical Race 4 - Raquel Correa-Delgado; Patricia Brito-López; Rosa E. Cardoza; María C. Jaizme Vega; Federico Laich; Santiago Gutiérrez (Agriculture)
The Canary Islands lead banana (Musa acuminata) production in the EU. Different fungal pathogens affect this crop in subtropical areas, with Fusarium oxysporum f. sp. cubense subtropical race 4 (Foc-STR4) being the most important in the Canary Islands. With the aim of developing environmentally sustainable techniques for disease control, this study presents the results of the evaluation of the antifungal capacity of a native Trichoderma collection (12 species, 109 isolates) obtained from banana soils. The results demonstrate the diversity of biocontrol genes and the in vitro antagonistic potential of different native Trichoderma species/isolates against two Foc-STR4 strains obtained from plants with Panama disease symptoms. Trichoderma virens (TF18), a dominant species in banana soils in the Canary Islands, showed a high capacity to inhibit the growth of Foc-STR4 in different in vitro assays. Trichoderma atrobrunneum (TF01) showed mycoparasitism capacity through the spiral coil around the hyphae of the pathogen. In addition, the genome analysis of T. atrobrunneum (TF03) showed 69 putative biosynthetic gene clusters, with the notable presence of the trichothecene tri5 gene. Finally, our work demonstrates that the soils of the Canary Islands banana crops are a potential source of environmentally adapted biological control agents to control or reduce the incidence of Foc-STR4.